Preparation, Culture, and Analysis of Amniotic Fluid Samples. (28th June 2018) - Miron, Patricia Minehart
Abstract: Amniotic fluid obtained via amniocentesis provides a source of fetal material used in prenatal diagnosis. The fluid may be used directly for biochemical analyses, fluorescence in situ hybridization (FISH), and isolation of DNA for molecular studies, including chromosomal microarray analysis (CMA). The fluid is typically cultured as a source of metaphase cells for chromosome analysis and to provide additional material for biochemical and DNA‐based testing. This unit describes an in situ method for the preparation, culture, and harvest of amniotic fluid samples for metaphase chromosome analysis. Cells are grown, harvested for metaphase spreads, and analyzed on glass coverslips. The unit also describes methods to obtain cells for additional studies (such as molecular genetic analyses) by growing cells in flasks either following passaging of cells from a glass coverslip culture or by directly establishing a flask culture from the amniotic fluid specimen. When cells are grown in flasks, they must be removed from the flask with trypsin before they can be used in studies. Lastly, this unit describes a method for isolating DNA for CMA from uncultured amniotic fluid and cultured cells. © 2018 by John Wiley & Sons, Inc.